Pengaruh Media Smart Box Terhadap Peningkatan Hasil Belajar Siswa SD Materi Kekayaan Budaya Indonesia - Putri Zahra Alifah; Tin Rustini; Agus Mulyana (Educatio, 2025)
This study aims to determine the effect of using smart box media on improving the learning outcomes of elementary school students on the material of Indonesian Cultural Wealth. The background of this study is the low interest and learning outcomes of students in cultural materials, as well as the lack of utilization of interesting interactive learning media. The method used was a quasi-experiment with a nonequivalent control group design, involving fourth grade elementary school students in Sukabumi Regency. The subjects were divided into two groups, namely the experimental group using smart box media and the control group using interactive power point media. Data was collected through pre-test and post-test consisting of multiple choice questions and essays to measure the improvement of students' understanding. The results showed that the experimental group experienced a more significant increase in learning outcomes than the control group. The highest post-test score in the experimental group reached 100 and the lowest 75, while the control group had the highest 96 and the lowest 65. Statistical analysis with t-test showed a significant difference between the two groups (p < 0.05). These findings indicate that smart box media can effectively increase student engagement and understanding of cultural concepts. Therefore, smart box media is recommended as an alternative contextualized interactive learning media that can support the learning process in elementary schools.